If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -5) + 7x = 5x + -25 Reorder the terms: 3(-5 + x) + 7x = 5x + -25 (-5 * 3 + x * 3) + 7x = 5x + -25 (-15 + 3x) + 7x = 5x + -25 Combine like terms: 3x + 7x = 10x -15 + 10x = 5x + -25 Reorder the terms: -15 + 10x = -25 + 5x Solving -15 + 10x = -25 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -15 + 10x + -5x = -25 + 5x + -5x Combine like terms: 10x + -5x = 5x -15 + 5x = -25 + 5x + -5x Combine like terms: 5x + -5x = 0 -15 + 5x = -25 + 0 -15 + 5x = -25 Add '15' to each side of the equation. -15 + 15 + 5x = -25 + 15 Combine like terms: -15 + 15 = 0 0 + 5x = -25 + 15 5x = -25 + 15 Combine like terms: -25 + 15 = -10 5x = -10 Divide each side by '5'. x = -2 Simplifying x = -2
| -2x^6-8x^5+64x^4=0 | | -4(2x-3)-2x=-8 | | 2xx+2x+2=0 | | 11x-4-6x=3x+10 | | 6x+5=3x+11 | | 5(x-4)+x=16 | | 15m^2=76m-5 | | -19+6-(-9)-10+18= | | -10x+3=-3x+24 | | 5x+3=27 | | 8x-19=-3 | | 7x-15=3x+1 | | n+s=926 | | (-4m+3)+(-m+6)-3= | | s+n=926 | | x^2-18+81=0 | | 24=6x+4(3x-3) | | 3x-22=3+4x | | 0.4n-18=3n-16-0.8 | | 3x^3+x^2-13x+5=0 | | 4x+3=9-2x | | 14p=7000 | | 3*0=6*-5+15 | | 3(-2)=6*1+15 | | p+13n=7000 | | 2x+3=6-x | | 3(-2)=6(1)+15x | | 26-8= | | 12p=13000 | | y=3-6 | | 13x=7000 | | 5y-8+y=16+3y-5y |